Фактори, що впливають на продуктивність екскаваторів при розробці бурштину з використанням напівмобільного збагачувального устаткування - Малоок О. В. (НТУ "ДП", 2025)
Дослідженні технологічні схеми роботи навантажувального обладнання, що дозволило отримати кути повороту бази екскаватора з ківшем від вибою до напівмобільної збагачувальної установки. Отримані графічні залежності кутів повороту ківша при відпрацюванні вибою біля напівмобільної збагачувальної установки, а також встановлено залежність зміни довжини секції (блоку) відпрацювання бурштинової ділянки при використанні екскаваторів JCB 220 зі звичайної стрілою та рукояттю і з подовженою рукояттю JCB 220 long reach. В роботі вперше отримана залежність визначення довжини секції з урахуванням довжини напівмобільних збагачувальних установок різної продуктивності. The technological schemes of loading equipment operation were studied, which made it possible to obtain the angles of rotation of the excavator base with a bucket from the working face to the semi-mobile enrichment plant. Graphical dependencies of the bucket rotation angles when working at the face near a semi-mobile enrichment plant were obtained, and the dependence of the change in the length of the section of the amber area when using JCB 220 excavators with a conventional boom and arm and with an extended JCB 220 long reach arm. The work is the first to determine the dependence of the section length on the length of semi-mobile enrichment plants of different capacities. It has been established that as the height of the ledge increases, the minimum length of the section decreases, and this is due to the fact that an increase in the height of the ledge leads to a decrease in the scoop radius of the excavator with an extended arm.
Factors affecting the productivity of excavators in amber mining using semi-mobile enrichment plants
Keywords: гірничі роботи; технологічна схема розробки; бурштин; технологічні параметри; напівмобільна збагачувальна установка; розробка родовища.; mining operations; technological development scheme; amber; technological parameters; semi-mobile enrichment plant; deposit development.